UPAH JURU KUNCI MAKAM BATU LAYANG PONTIANAK TINJAUAN KOMPILASI HUKUM EKONOMI SYARIAH - Syarifah Nur Halimah; Abu Bakar; Nur Hakimah (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2023)
This study aims to find answers to the main problems, namely the system of caretaker services for the Batu Layang Pontianak tomb and the legal fees for caretakers for the Batu Layang Pontianak tomb in the review of the Sharia Economic Law Compilation (KHES). This type of research uses qualitative methods and a normative-empirical approach. Researchers collect primary data from observations, interviews, and documentation, while secondary data researchers obtain from literature, articles, journals, and websites. Based on the results of the study it can be concluded that: 1) The caretaker of the Batu Layang tomb applies two practices, namely wages from pilgrims who are voluntary and wages from the Pontianak Cultural Heritage Service worth IDR 1,000,000.00 per month. 2) The law on the wages of caretakers of the Batu Layang tomb in KHES has complied with and is by the provisions in the ijarah chapter, namely pillars and ijarah contracts, and is not contradictory. However, there is one article that is inconsistent with the caretaker wages for the caretaker of the Batu Layang Pontianak tomb, namely article 311. The results of this study indicate that concerning pilgrims if they do not require the services of a caretaker, they will not receive ijarah. However, the caretaker always does the work in his contract with the Pontianak Cultural Heritage Service.